Effect of Contact Time and Gas Component on Interfacial Tension of CO2/Crude Oil System by Pendant Drop Method - Xin Wang; Lifeng Liu; Zengmin Lun; Chengyuan Lv; Rui Wang; Haitao Wang; Dong Zhang (Journal of Spectroscopy)
Pendant drop method has been used to measure the equilibrium interfacial tension and dynamic interfacial tension of CO2/crude oil system under the simulated-formation condition, in which the temperature is 355.65 K and pressure ranges from 0 MPa to 30 MPa. The test results indicated that the equilibrium interfacial tension of CO2/crude oil systems decreased with the increase of the systematic pressure. The dynamic interfacial tension of CO2/original oil, CO2/remaining oil, and CO2/produced oil systems is large at the initial contact and decreases gradually after that, and then finally it reaches dynamic balance. In addition, the higher the pressure is, the larger the magnitude of changing of CO2/crude oil interfacial tension with time will reduce. Moreover, by PVT phase experiment, gas-oil ratio, gas composition, and well fluid composition have been got, and different contents of light components in three oil samples under reservoir conditions have also been calculated. The relationship between equilibrium interfacial tensions and pressures of three different components of crude oil and CO2 system was studied, and the higher C1 is, the lower C2–C10 will be, and the equilibrium interfacial tension will get higher. Therefore, the effect of light weight fractions on interfacial tension under formation conditions was studied.